Orogenic gold deposits: part of a global dynamic conjunction between subduction and gold. Issue 1 (1st December 2019) - Groves, David I.
Summary: Orogenic gold deposits represent a coherent deposit class that were deposited from low-salinity CO2-rich fluids over a range of crustal depths from 3 to 20 km. They are widely considered to have formed from crustal metamorphic fluids generated at the amphibolite-greenschist-facies transition. However, recent research, particularly in China, shows that only a sub-crustal source of fluid is viable and that devolatilization of subduction slabs and overlying sediment wedges is the most plausible source of the auriferous fluids. An alternative source is devolatilization of fertilized mantle lithosphere that was earlier metasomatized by subduction-related fluids. This recognition of a subduction-related origin allows the orogenic gold deposits to be placed into a coherent, subduction-related dynamic model in which all epigenetic gold deposits formed during evolution of a convergent margin. The earliest deposits that formed from subduction-related magmatic-hydrothermal fluids during mild compression are inter-related porphyry Cu-Au, high-sulfidation epithermal Ag-Au and skarn deposits in volcanic and continental arcs. Subsequent mild extension resulted in formation of low-sulfidation epithermal Ag-Au in volcanic and continental back-arcs and gold-rich VMS systems in volcanic back-arcs. Orogenic gold deposits then developed under transpression during late orogenesis in the convergent margin. The initiation of orogenic collapse saw the formation of IRGDs and Carlin-type gold deposits related to hybrid magmas, formed by melting of subduction-related metasomatized lithosphere, in far back-arc environments. Finally, following supercontinent assembly, IOCG deposits formed on the margins of continental blocks during extension, mantle up-welling and melting of subduction-related fertilized lithosphere that released highly volatile magmatic-hydrothermal fluid systems into the crust.